A desigualdade espacial do baixo peso ao nascer no Brasil - Lima, Marina Clarissa Barros de Melo (2012)
Background:Low birth weight(LBW) isa risk factor formorbidity, infant and child mortality. In Brazilthe highest percentages oflow birth weightoccur inregionsofbettersocio-economic status. Objective: to know the spatial distributionofrates of lowbirth weight andcorrelation withsocial indicatorsand service. Drawing: ecological, and Brazilian statesas units ofanalysis. Methodologyused thetechnique ofspatial analysis, data from 2009SINASC, IPEAandIBGE. Results:higher rates oflow birth weightare in the statesof the south/southeast,GlobalMoran: 0.267, p=0.02.Clustersofhigh-hightypein the Southeastandlow-lowstates ofthe Amazon region.Conclusion: Thespatial inequalityoflow birth weightreflectsthe socioeconomic conditionsof the states. More developed regionsholdhigher rates oflow birth weight, therefore,the presenceof the serviceandits usedodecrease infant mortalityandincrease theBPN